Study of cosmic evolution admitting thermodynamic analysis - M. Sharif; M. Zeeshan Gul; Nusrat Fatima (European Physical Journal C: Particles and Fields)
Abstract This article examines the cosmic evolution in the framework of symmetric teleparallel theory, characterized by the function of non-metricity scalar $$(\mathcal {Q})$$ ( Q ) . We use the e-folding number and reconstruction method with a suitable parametrization of the scale factor to obtain the functional form of symmetric teleparallel theory. Using this reconstructed model, we examine the behavior of different cosmographic parameters to demonstrate the bouncing scenarios of the cosmos by considering the contraction and expansion phases of cosmos before and after the bouncing point, respectively. It is found that the null energy condition is violated which shows that the singularity issue can be resolved in this extended theoretical framework. Moreover, we observe that the acceleration occurs near the bouncing point and the reconstructed model aligns with the current cosmic expansion. Finally, we check the validity of second law of thermodynamics in the bouncing framework of our model.